(untitled) (Research, Society and Development, 2024)
Introduction: The aging of the Brazilian population is a growing process and significantly impacts PHC (Primary Health Care). Objective: To analyze, based on the literature of the last five years, the perception and access of the elderly in the Family Health Strategy (ESF). Methods: Quantitative review, carried out in LILACS and SCIELO databases. The inclusion criteria were articles from 2020-2024, presented in full text and free of charge. Excluding articles presented in annals, incomplete and without reference to the topic addressed. Results: It was evident that, in the perception of the elderly, the public service has improved, but difficulties in access and dissatisfaction with the quality of some persist. This leads to the search for secondary care, emergency care, and private medicine. Problems were identified in in-home care, the health care network, and interprofessional work. The teams offer practices under the biomedical model and are centered on the medical professional, although health promotion and disease prevention actions were identified. Regarding the attributes of PHC, the results showed that frail elderly individuals, compared to robust ones, presented greater problems with access, longitudinally, and comprehensiveness in health care. Conclusion: In the view of the elderly, the expansion of the ESF in Brazil has played a fundamental role in expanding access and improving the quality of health services. However, some areas still need improvement to serve this population.